Most frequent comorbidities in a geriatric outpatient at a teaching hospital (Research, Society and Development, 2022)
The study aimed to characterize the most prevalent pathologies at outpatient level in a first geriatric consultation between from 2016 to 2019 in a teaching hospital in Belém do Pará. Data was collected from the medical records of Hospital Jean Bittar in the period described above, using a Term of Consent for the Use of Data (TCUD) and having a sample of 211 records. Among the main morbidities identified in the analyzed period, there is a predominance of Hypertension as the main morbidity throughout the study period. There is a significant percentage of cases of Type 2 Diabetes Mellitus, followed by Neoplasms, Osteoarthritis and Obesity. It is concluded that it is necessary to promote research related to the aforementioned diseases, as they affect a significant portion of the population.